Ethical Capital as a Value Proposition in Halal Tourism Entrepreneurship: Evidence from Lombok, Indonesia - Pratama, Aryan Agus; Feriyadin, Feriyadin; Ulya, Baiq Nikmatul; Maswandi, Ega Dwi Putri (Universitas Negeri Makassar, 2026)
Halal tourism studies have thus far been dominated by attributive and symbolic approaches, while the value dimensions underlying destination practices and sustainability have not been explored in depth. This study aims to investigate the value proposition underlying Lombok's halal tourism branding. The study uses a qualitative approach with a case study design in two community-based destinations. Data were collected through observation, in-depth interviews, and focus group discussions, then analyzed using content analysis through the stages of data condensation, data presentation, and conclusion drawing. The results show that halal tourism practices in Lombok are shaped by ethical capital consisting of social dedication, understanding of halal, and obedience, which serve as the foundation of the destination's value proposition. These findings confirm that the sustainability and credibility of Lombok's halal tourism branding depend on the strength of local values that live within the business community, so that halal destination development strategies need to be directed at strengthening community values and involvement, not merely symbolic promotion.